Investigation of Programmed Cell Death-1 (PD-1) Gene Variations at Positions PD1.3 and PD1.5 in Iranian Patients with Non-small Cell Lung Cancer. - Pirdelkhosh, Zahra; Kazemi, Tohid; Haghshenas, Mohammad Reza; Ghayumi, Mohammad Ali; Erfani, Nasrollah (Middle East Journal of Cancer, 2018)
Background: Tumor cells express PD-1 ligands to bind PD-1 on immune cells and escape immune responses. In the present study, we aimed to investigate whether single nucleotide polymorphisms at positions PD1.3 (+7146, rs11568821) G/A, and PD1.5 (+7785 C/T, rs2227981) may be considered risk factors for susceptibility to nonsmall cell lung cancer in the Iranian population. Methods: This study enrolled 206 histopathologically confirmed lung cancer patients and 173 age/sex matched healthy controls. We performed PCR-RFLP to determine the genotypes of the extracted genomic DNA. Results: The frequencies of PD1.3 GG, GA and AA genotypes were 171 (83%), 31 (15%) and 4 (1.9%) out of 206 patients, and 144 (83.2%), 26 (15%), and 3 (1.7%) out of 173 controls, respectively. The frequencies of PD1.5 CC, CT and TT genotypes were 78 (37.9%), 100 (48.5%), and 28 (13.6%) in patients, and 60 (34.7%), 89 (51.4%), and 24 (13.9%) in controls. There were no significant differences in genotype analysis between patients and controls at positions PD1.3 (P=0.98) or PD1.5 (P=0.80). No significant differences existed in the frequencies of alleles and haplotypes between the two groups (P>0.05). Conclusion: Our data have indicated no association between PD1.3 (+7146) G/A and PD1.5 (+7785) C/T with susceptibility to non-small cell lung cancer. Investigation of other PD1 genetic variations and emerged haplotypes are required to completely define the role of PD1 genetic variations in susceptibility to lung cancer.